1)(x-3)(3x+2)=(5x-4)(3x-2)x*3x+2x-3*3x-6=5x*3x-5x*2-4*3x+83x^2+2x-9x-6=15x^2-10x-12x+83x^2-15x^2-7x-6=-22x+8-12x^2+15x+14=012x^2-15x-14=02)(2x+7)(7-2x)=49+x·(x+2)7*2x-2x*2x+7*7-7*2x=49+x^2+2*x14x-4x^2+49-14x=49+x^2+2x-4x^2+49-49=x^2+2xx^2+2x=-4x^2x^2+4x^2+2x=05x^2+2x=0, где с=03)3x-2\2x+1=2x+3\2x-1(2x-1)(3x-2)-(2x+1)(2x+3)=02x*3x-2x*2-1*3x+2-2x*2x-3*2x+2x+3=06x^2-4x-3x+2-4x^2-6x+2x+3=06x^2-4x^2-7x-6x+2x+2+3=02x^2-11x+5=04)x-1\x+3+5x-4\4x+1=1(4x+1)(x-1)+(x+3)(5x-4)=(x+3)(4x+1)4x*x-4x+x-1+5x*x-4x+3*5x-3*4=x*4x+x+3*4x+34x^2-3x-1+5x^2-4x+15x-12=4x^2+x+12x+3x^2: 4x^2+5x^2-4x^2x:-3x-4x+15x-12x-xx^0:-1-12-35x^2-5x-16=0